Are there International Labour Standards? Case of Migrant Workers’ Exploitation in Italy - Gunawan, Yordan; Ansar, Muhammad Arya; Fathi, Muhammad; Devty, Stephanie; Irrynta, Dwilani (Jurnal Mulawarman Law Review, 2022)
The increasingly fierce competition in the world of work has an impact on people getting jobs. The condition makes most people become migrants by traveling to other countries to find a job for a decent life in the future. However, the work that migrant workers get is often not as expected, so the rights of migrants are often not fulfilled. The amount of violence in the world of work and the non-fulfillment of the rights of migrant workers in Italy is an act that violates human rights. Therefore, the authors wrote this article by using normative legal research method to analyze migrant workers in Italy who are exploited by forced labor and the lack of protection regarding the minimum wage for migrant workers and also aims to analyze the role of the International Labour Organization as an organization that protects the rights of migrant workers, including protection from violence and protection of the minimum wage for migrant workers in Italy. The result shows that there is an urgency for Italy to ratify the Minimum Wage Convention on the grounds that it diminishes the exploitation of migrant workers and provides binding legal force for the sake of migrant workers.